Performance after damages and repairs to polymeric composites - Muhammad Muffies Majharudeen (Nanyang Technological University, 2021)
The purpose of the project is to review failures of composites and degradation of their performance in aerospace applications. This report is also aimed at the repair of composites in aerospace and the recovery of their performance. Several cases were studied to analyse the most common types of composite repair. Resin injection repair and scarf angle repair of composites were selected to study further the efficiency of the repair. It was found that such cases are limited and not much of experimental data is available to draw useful inferences or guidelines for future. With the small datasets available from past studies, knowledge-based data boosting (KBDB) process has been applied to each individual case studies. The KBDB process adds more data points to the given research reliably to achieve an authentically boosted dataset. In hand, helping to build a predictive model for future studies on composite performance and repair. The KBDB process enabled further understanding of the individual repair efficiencies with regards to their independent variables. R² value of original and boosted data were studied together with the boosting factor. With the aid of KBDB process, it is noteworthy to conclude that scarf angle of less than 4.5° are optimum for scarf angle repair and delamination area of less than 20% is suitable for resin injection repair.